BRAIDED STORIES AND BRICOLAGED SYMBOLS: CRITICAL REFLECTION AND TRANSFORMATIVE LEARNING THEORY FOR TEACHERS - Brigham, Susan Mary (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
ABSTRACT: In this paper I make the case that transformative learning theory, a specific adult learning theory, and an arts-informed research method have important value for teacher professional practice and teacher education. I refer to two phases of a study involving women who have immigrated to Maritime Canada and were teachers in their countries of origin. I illustrate a process through which participants can weave multiple perspectives, unpack constructed realities, and become more reflective about their teacher identity and teaching practice. HISTOIRES MÉTISSÉES ET SYMBOLES FABRIQUÉS: RÉFLEXION CRITIQUE ET THÉORIE DE L’APPRENTISSAGE PAR TRANSFORMATION POUR LES ENSEIGNANTS RÉSUMÉ. Par le biais de cet article, je démontre que la théorie de l’apprentissage par transformation, une théorie de l’apprentissage associée aux clientèles adultes et une méthodologie de recherche axée sur les arts, se révèle d’une valeur cruciale pour la pratique professionnelle des enseignants ainsi que la formation des maîtres. Pour ce faire, je fais référence aux deux phases d’une étude impliquant des femmes enseignantes dans leur pays d’origine et ayant immigré dans la région canadienne des Maritimes. J’illustre le processus au cours duquel les participantes peuvent développer de multiples perspectives, déconstruire leur perception de la réalité et devenir davantage réfléchies quant à leur identité et leur pratique enseignantes.